The research equity and diversity initiative (READI): Changing the face of clinical research through community outreach and engagement - Sally Taylor; Stephanie Freel; Lynn Sutton; Kenisha Bethea; Leatrice Martin; Julie McKeel; Matthew Ray; Perusi B. Muhigaba; Stella Quenstedt; Amanda McMillan; Taryn Cavanaugh Faulk; Jenifer Allen; et al. (Journal of Clinical and Translational Science)
Current evidence underscores a need to transform how we do clinical research, shifting from academic-driven priorities to co-led community partnership focused programs, accessible and relevant career pathway programs that expand opportunities for career development, and design of trainings and practices to develop cultural competence among research teams. Failures of equitable research translation contribute to health disparities. Drivers of this failed translation include lack of diversity in both researchers and participants, lack of alignment between research institutions and the communities they serve, and lack of attention to structural sources of inequity and drivers of mistrust for science and research. The Duke University Research Equity and Diversity Initiative (READI) is a program designed to better align clinical research programs with community health priorities through community engagement. Organized around three specific aims, READI-supported programs targeting increased workforce diversity, workforce training in community engagement and cultural competence, inclusive research engagement principles, and development of trustworthy partnerships.